Ancient readers and their scriptures : engaging the Hebrew Bible in early Judaism and Christianity - Allen, Garrick V.; Dunne, John Anthony, 1986- (Ancient Judaism and early Christianity ;, 2019)
Ancient Readers and their Scriptures explores the ways that ancient Jews and Christians interpreted the Hebrew Bible in antiquity, focusing on the processes of reading that are preserved in the textual and material record of the corpora that engage Jewish scripture.